Pendidikan Karakter Melalui Pembelajaran Tahfidz Al-Qur’an Berbasis Metode Ummi Bagi Siswa SDIT Salsabilla Sleman - Fauzi, Hafidh Nur; Waharjani, Waharjani (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This study aims to determine the steps of character education through the Al Qur`an SDIT Salsabila 8 Sleman tahfidz program, to identify the character values of Salsabila 8 Sleman SDIT students through the Al Quran tahfidz program, and to determine the evaluation of character education through the Al Quran tahfidz program. This study uses a qualitative descriptive study with data triagulation analysis techniques. To obtain information the researchers used interview, observation and documentation techniques with the subject of the teacher and the principal. Based on the results obtained: Steps in character education through learning the Koran tahfidz at SDIT Salsabila; 1) Preparing the teaching staff, 2) mapping the levels of students, 3) Grouping, 4) Making a schedule, 5) implementation. Implementation of character values that are applied through learning Tahfidz Al Qur'an at SDIT Salsabila 8 Sleman there are 18 characters, but there are 7 dominant character values that appear including: 1) Religion, 2) honest, 3) hard work, 4) fond of reading, 5) creative, 6) responsible, and 7) discipline. Evaluation of character learning through Al Quran tahfidz education at SDIT Salsabila 8 Sleman has been going well where students will be evaluated daily and at the end of the semester by examiners and controlled through achievement books.